Study on Analysis and Design of Suspension Cable Bridge Using SAP2000 - Darius Angtony; Andri Irfan Rifai; Mulia Pamadi; Muhammad Isradi (Jurnal Syntax Transformation, 2024)
Bridges are more than just physical structures; they connect people and places, facilitating commerce, transportation, cultural exchange, and shaping landscapes. Bridges are complex structures composed of various essential components, including the auxiliary building, substructure, and superstructure, each crucial for the overall stability and functionality. Engineers face challenges in bridge construction, including environmental conditions, traffic volumes, and geological threats. Additionally, aging infrastructure and financial constraints make bridge rehabilitation and maintenance increasingly difficult. This research will focus on the analysis and design of suspension cable bridges, a unique type of bridge that leverages tension and compression for structural effectiveness. This research will utilize the SAP2000 software, a sophisticated application for structural analysis and design used by civil engineers, architects, and construction experts to model, evaluate, and design various structures, including buildings, bridges, dams, and towers. The methodology employed in this study is consistent with qualitative research approaches that aim to understand better social phenomena, cultural contexts, and human behavior. The analysis and design of the suspension cable bridge using SAP2000 will be the primary focus of this study. This will involve a detailed examination of the necessary components and construction techniques for suspension bridges. The various loads a bridge may encounter over its lifetime will be carefully considered during the structural design process, as these loads significantly impact the bridge's longevity, stability, and safety. The findings of this research are expected to provide a comprehensive understanding of the analysis and design of suspension cable bridges using the SAP2000 software. The insights gained from this study will contribute to developing more effective and efficient bridge construction technologies, addressing the ongoing challenges engineers face in the field.